Predictors of infertility-related concerns in a Canadian survey of men and women seeking fertility treatment. Issue 9 (September 2020) - Gelgoot, Eden Noah; Kelly-Hedrick, Margot; Miner, Skye A.; Robins, Stephanie; Chan, Peter; Ells, Carolyn; Holzer, Hananel; Lo, Kirk; Mahutte, Neal; Ouhilal, Sophia; Tulandi, Togas; Zelkowitz, Phyllis
Highlights: The correlates of levels of infertility-related concerns differed in men and women. Men who were religious and in infertility treatment for longer had more concerns. More educated and childless women had more infertility-related concerns. Men and women with more concerns reported higher stress. Certain patients wanted to discuss psychosocial issues with healthcare providers. Abstract: Objective: To examine if and how factors associated with infertility-related concerns and opportunity to discuss concerns differ between male and female fertility patients. Methods: A cross-sectional survey of 313 female and 254 male patients recruited from Canadian fertility clinics. An online survey asked about sociodemographic characteristics, psychological distress, the severity of psychosocial concerns on a scale of 0 (not concerned) to 5 (very concerned) related to fertility treatment, and their opportunity and desire to discuss concerns with healthcare providers (HCPs). Results: For women, higher stress, educational attainment and being childless were associated with higher concern ( F (6, 287) = 14.73, p < .001). For men, higher stress, being religious and longer treatment duration were associated with higher concern ( F (8, 222) = 9.87, p < .001). No significant difference existed between men's and women's average concern scores ( t (558) = -1.62, p = .11) or opportunity to discuss concerns ( t (149) = 0.28, p = .78). Conclusion: Our results indicate an unmet need and desire for support among subgroups of patients who were concerned about psychosocial issues related to infertility, but did not have the opportunity to discuss these issues with HCPs. Practice Implications: There is a need to tailor resources to address the concerns of male and female fertility patients from diverse sociodemographic backgrounds and with different fertility histories.